Tiny goat in trouble - Kelly, Mary; Davis, Jon (London : Scholastic, 2014)
Harry is enjoying a seaside walk with his aunt, when he spots a tiny goat on a cliff ledge. It has been separated from its mother, and the baby goat is stranded, unable to make it back up to the top. Harry and his aunt call the RSPCA and an exciting rescue ensues, with two inspectors abseiling down the cliff to retrieve the frightened youngster. Luckily, thanks to the RSPCA's team work and Harry's eagle eye, the baby goat is safely reunited with its mother. An exciting, inspiring story based on a real-life animal rescue. With illustrations throughout and lots of facts about goats and the RSPCA.
b
b
Keywords: Animals